Development of a 4DoFs exoskeleton robot for passive arm movement assistance. (1st January 2012) - Rahman, Mohammad H.; Ouimet, Thierry K.; Saad, Maarouf; Kenné, Jean P.; Archambault, Philippe S.
Proper functioning of the upper limbs is important to manage essential activities of daily living. To provide assistance and rehabilitation to individuals with upper limb dysfunction due to conditions such as stroke or spinal cord injuries, we have developed a 4DoFs exoskeleton robot (ExoRob). The ExoRob was designed to be worn on the lateral side of the upper arm, to conform to a naturalistic range of movement for the shoulder and elbow joints. This paper focuses on the modelling, design, development, and control of the ExoRob. Experiments were carried out with healthy human subjects where trajectories tracking in the form of passive rehabilitation exercises were performed. Further experiments were carried out with the master exoskeleton arm (mExoArm, an upper-limb prototype exoskeleton arm) where subjects operate the mExoArm (like a joystick) to maneuver the ExoRob to provide passive rehabilitation. Experimental results show that the ExoRob can effectively perform passive rehabilitation exercises.